Stratigraphy, structure and metamorphic petrology of the Turner Lake area, Archean Slave Province, Northwest Territories. - Schaan, Susan. (University of Ottawa (Canada), 1994)
Lithological, metamorphic and structural relationships are established in the Turner Lake area of the Archean Hood River supracrustal domain. Four map units define a stratigraphic sequence of subvertical beds that appears to young eastward. Metamorphosed greywacke to mudstone turbidites (Unit 1) are overlain with local discordance by polymict conglomerate (Unit 2, James Falls Conglomerate) with clasts mainly of diorite, volcanic and sedimentary rocks interpreted to be of local origin. An intercalated metamorphosed sequence (Unit 3) of arenite, layered volcaniclastic rocks, breccia and conglomerate (including tonalite cobbles), pyroxenite and dioritic to gabbroic intrusions, is apparently overlain further east by a second sequence (Unit 4) of greywacke-mudstones. Sheet-like trondhjemitic to tonalitic intrusions, one with a U-Pb zircon age of 2607 $\pm$ 1.3 Ma, are common within Unit 3; minor tonalitic sheets intrude Unit 1. Larger plutons include the (2600 $\pm$ 2 Ma, U-Pb zircon) Pistol Lake granodiorite to tonalite in the south and the Fish-hook Lake monzogranite in the west. Proterozoic diabase dykes of at least three ages cross-cut the Archean rocks. Metagreywacke-mudstones of Units 1 and 4 have similar rare earth element signatures and may be derived from a similar source terrane. The signatures resemble those of Yellowknife Supergroup metasedimentary rocks in the Yellowknife area. Trace element signatures of epiclastic amphibolites and mafic tuffs suggest mixed ultramafic and felsic sources. They may be consanguineous with the metapyroxenite. Highly foliated tonalite sheets and less deformed trondhjemite sheets have similar whole rock and rare earth element signatures to the Pistol Lake pluton. The lack of negative europiom anomalies in the rare earth element signatures of the plutonic rocks is comparable to synkinematic granites in the Yellowknife area. (Abstract shortened by UMI.)
Keywords: Geology.